Latihan Peningkatan Kemampuan Biomotor (Kelincahan, Kecepatan, Keseimbangan Dan Fleksibilitas) Dengan Teknik Lari (Shuttle Run, Zig-Zag, Formasi 8) Pada Pesilat - Bambang Trisnowiyanto (Jurnal Keterapian Fisik, 2016)
Abstract : Biomotor Components (Agility, Speed, Flexibilty, Balance), Pencak Silat Athlete. Biomotor such as agility is one of components must had had been own by athlete as physical condition indicator for exellence performance in competition. Agility perform with abilty change of direction and body position in fast and exact at movement without lossing balance and conscious of body position. The purpose of the study was to know influence of agility exercise model for agility, speed, flexibilty and balance in pencak silat athlete. Also to know whereas the efective model of agility exercise can improve physical ability of pencak silat athlete. This research is quantitative research, with quasi experiment design three treatment counterbalance-balance. Data analyses uses Wilcoxon test and Kruskal Wallis test. For measure improvement uses mean different. The significance satandart is p=0.05 (5%). Research result are : There is significant comparation between shutle run, zig-zag run, zig-zag combine 8 numeral run, for agilty and speed (p<0.05), shutle run useful for improve balance and speed, zig-zag run useful for improve agility and zig-zag combine 8 numeral run usefull for improve flexibility.